1990
DOI: 10.4098/at.arch.90-36
|View full text |Cite
|
Sign up to set email alerts
|

Diet and habitat selection of the pine marten in relation to competition with the red fox

Abstract: Diet and habitat selection of the pine marten in relation to competition with the red foxUse STORCH, Erik LINDSTROM and Jonas de JOUNGE Storch I.. Lindstrom E. and de Jounge J. 1990. Diet and habitat selection of the pine marten in relation to competition with the red fox. Acta theriol. 35: 311 -320.After a reduction in red fox Vulpes vulpes Linnaeus, 1758 density in south-central Sweden due to an epizootic of sarcoptic mange, which reached the study area in 1982, pine martens Martes martes Linnaeus. 1758 beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
2
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 12 publications
7
93
2
2
Order By: Relevance
“…European carnivore community trophic niche composition and overlap has been shown to be conservative and similar across species. The majority of the community comparisons have addressed the overlap between martens and the red fox, describing their feeding habits as opportunistic, with availability playing a major role in prey selection patterns (Goszczynski 1986, Storch et al 1990, Serrafini and Lovari 1993, Lanszki et al 1999, Padial et al 2002. Our results corroborate the high degree of overlap between these two species found in other Mediterranean areas (Serafini and Lovari 1993).…”
Section: Diet Of Carnivoressupporting
confidence: 81%
See 1 more Smart Citation
“…European carnivore community trophic niche composition and overlap has been shown to be conservative and similar across species. The majority of the community comparisons have addressed the overlap between martens and the red fox, describing their feeding habits as opportunistic, with availability playing a major role in prey selection patterns (Goszczynski 1986, Storch et al 1990, Serrafini and Lovari 1993, Lanszki et al 1999, Padial et al 2002. Our results corroborate the high degree of overlap between these two species found in other Mediterranean areas (Serafini and Lovari 1993).…”
Section: Diet Of Carnivoressupporting
confidence: 81%
“…Our results also corroborate this increased dietary richness in diet. The red fox, however, has been considered to be one of the most generalist carnivores in Europe (Sweden: Storch et al 1990;Poland: Goszczynski 1974Hungary: Lanszki et al 1999;France: Artois et al 1982;Artois 1989;Italy: Serafini and Lovari 1993) and in Mediterranean habitats, where the red fox has been described as feeding on a large range of prey (Italy: Serafini and Lovari 1993;Spain: Calviño et al 1984, Padial et al 2002. However, our data contradict this pattern, with the red fox being the least generalist of the four species studied, but still with a high plasticity in food habits.…”
Section: Diet Of Carnivoresmentioning
confidence: 99%
“…Research carried out so far (eg Nasimovic 1948, Hoglund 1960, Weckwerth and Hawley 1962, Danilov and Tumanov 1976, Goszczyński 1976, Morozov 1976, Pulliainen 1981a, Zieliński et al 1983, Buskirk and MacDonald 1984, Reig and Jędrzejewski 1988, Marchesi and Mermod 1989, Nagorsen et al 1989, 1991, Slough et al 1989, Storch et al 1990, Thompson and Colgan 1990 has shown that the Eurasian pine marten Martes martes (Linnaeus, 1758) and North American pine marten M. americana possess very similar food intake patterns, although the latter is smaller in size. These species are generally regarded as generalists and opportunists in their feeding behaviour, although Rosen zweig (1966) concluded that the North American pine marten is a microtine specialist.…”
Section: Introductionmentioning
confidence: 99%
“…These two methods are among the most common methodologies used to assess habitat selection or habitat use in carnivores, including the red fox (e.g., [12][13][14][15][16]). Contrary to snowtracking, radio-telemetry is invasive because it requires immobilizing and handling the animals.…”
Section: Data Collection and Analysesmentioning
confidence: 99%